MARKERS OF ENDOTHELIAL DYSFUNCTION AS CRITERIA FOR DESTABILIZATION OF THE DISEASE COURSE IN PATIENTS WITH CORONARY ARTERY DISEASE - Romanova, V.O.; Kuzminova, N.V.; Romanova, L.O.; Lozynskyi, S.E.; Kniazkova, I.I.; Kulchytska, O.M.; Shkarovskyi, Y.L. (World of Medicine and Biology, 2023)
To determine the presence and severity of vascular endothelial dysfunction in patients with coronary artery disease and the possibility of diagnosing exacerbation of the atherosclerotic process in such patients by determining markers of endothelial dysfunction, 173 patients with different variants of the disease were examined. It was found that patients with unstable coronary artery disease were characterized by a more pronounced impairment of vascular endothelial function, as evidenced by a significant increase in biochemical markers of endothelial dysfunction (ET-1, sVCAM, and PAPP-A) not only compared to the control group but also to the patients with stable coronary artery disease. Therefore, such markers can be considered criteria for destabilizing the atherosclerotic process. Based on determining the threshold values of endothelial dysfunction in patients with coronary artery disease, groups with definite and possible (“grey zone”) destabilization and without destabilization were identified. Values of ET- 1 ≥10.43 ng/mL, sVCAM ≥1320.0 ng/mL, and PAPP-A ≥10.10 mIU/L were the basis for including patients in the group of patients with a destabilization of the disease even in the absence of clinical manifestations.